Morphological and physiological changes induced by Achyranthes aspera-mediated silver nanocomposites in Aedes aegypti larvae - Sharma, Aarti; Mishra, Monika; Dagar, Vinay Singh; Kumar, Sarita (Frontiers in Physiology, 2022)
Aedes aegypti is responsible for the global spread of several ailments such as chikungunya, dengue, yellow fever, and Zika. The use of synthetic chemicals is the primary intervention in mosquito management. However, their excessive utilization resulting in the spread of toxic ingredients in the environment and posing threats to beneficial organisms has prompted the recommendation for the use of biologically synthesized nanocomposites as a promising approach for vector control. Silver nanocomposites were synthesized using leaf (AL-AgNCs) and stem (AS-AgNCs) extracts of Achyranthes aspera. The early fourth instars of A. aegypti were exposed to lethal doses of these nanocomposites to evaluate their effects on larval development, behavior, morphology, and mid-gut histoarchitecture. The cellular damage and deposition of nanocomposite residues in the mid-gut were studied using light and transmission electron microscopy. The A. aspera silver nanocomposite (AA-AgNC)-exposed larvae exhibited dose-dependent extended duration of development and diminished adult emergence, but did not exhibit modified behavior. Intense damage to the cuticle membrane and slight contraction in the internal membrane of anal papillae were noticed. Morphologically, the mid-gut appeared disorganized, darkly pigmented, and shrunk. Histological investigations of the mid-gut revealed significantly disordered internal architecture with lysed cells, damaged peritrophic membrane and microvilli, disintegrated epithelial layer, and a ruptured and displaced basement membrane. Visualization of the larval mid-gut through TEM showed severe cellular damage and aggregation of black spots, indicating the deposition of silver particles released by AA-AgNCs. The investigations revealed the bio-efficacy of A. aspera-mediated AgNCs against A. aegypti inducing stomach and contact toxicity in the larvae. The utilization of AA-AgNCs is recommended for A. aegypti management as a safe and effective intervention.